The effect of using the assemblr edu application as a media for learning subjects in science on students' interests and learning outcomes (case study: Bedug state primary school 01) - Triana, Vivit; Hariyastuti , Anik (Universitas Nusantara PGRI Kediri, 2024)
The digital era continues to evolve and has a significant impact on every aspect of life, including education. With the increasing digitization in the world of education, there are many choices of learning media that can be utilized for teaching and learning activities, one of which is Assembly Edu. This research aims to assess the extent of the influence of using Assemblr Edu on the interest and learning outcomes of students at SD Negeri Bedug 01 in the subject of Natural and Social Sciences. The research method employed is a quantitative research method. This study involved pre-tests and post-tests, as well as the formation of experimental and control groups to explore the experiences and outcomes of students using Assemblr Edu compared to the control group. The researcher found that there is a positive influence of using Assemblr Edu on the interest and learning outcomes of students. Statistical analysis shows a significant relationship between Assembly Edu and students' interest and learning outcomes. The results of this study provide an overview of the significant effects of information technology when used as a learning medium by teachers.